Herbicide Resistant Weeds - Curtis R. Rainbolt; Brent A. Sellers; Jason A. Ferrell; Greg E. MacDonald (EDIS)
Herbicide performance is a complex issue that is influenced by many factors. These include spray coverage, application method, herbicide rate, environmental conditions, and weed size, to name a few. Poor or incomplete control may also be due to the ability of a weed to tolerate a particular herbicide. Herbicide tolerance is the inherent ability of a species to survive following a herbicide treatment. There was no selection to make the plant tolerant; it simply possesses a natural tolerance. This document is SS-AGR-243, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date December 2005.